The thin veneer : 01110100 01101000 01100101 00100000 01110100 01101000 0110100101101110 00100000 01110110 01100101 01101 110 01100101 011001010111001 00001010 : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Griffiths, Belinda (Massey University, 2022)
As a multimedia artist and maker of digital objects I explore the metaphysical tension between reality and memory through the use of the intangible materials of light and projection. I have researched and explored immersive experiences that are ephemeral and contemplative through multi-sensory phenomena. Through creative research, I have investigated notions of what constitutes real when it is subverted by a pixelated-permeable boundary, the hyperreal, where the physical and virtual touch. Colliding virtuality by calibrating the notions of materiality and the immaterial, I place the observer on the threshold of a liminal blurred state between the two. As an artist, perhaps the question now is, not what is real, but what is real in an age of digital technology. Where the immaterial seeps into the material, embodied and corporeal.
Keywords: 360503 Digital and electronic media art